Pest Complex of Cultivated Oyster Mushroom in Northeast India: Feeding Losses and Role of Micro-climate in Pest Multiplication - Nongkynrih, B.; Firake, D. M.; Baiswar, P.; Behere, G. T.; Chandra, S.; Ngachan, S. V. (Indian Journal of Hill Farming, 2018)
The northeast India is one of the most promising regions for the cultivation of mushroom where oyster mushroom is a widely accepted and popular food among the local people.Despite higher demand, the year-round production of oyster mushroom is usually not possible, which is mainly due to severe damage by the insect pests and diseases, especially during rainy season. We studied the detailed pest complex of oyster mushroom, their damage pattern and the role of micro-climatic factors on pest multiplication during 2013 and 2014. Various arthropod pests viz., pleasing fungus beetles (Triplax spp., Scaphisoma spp. and Megalodacne spp.) sciarid fly (Bradysia spp.), mycetophilid fly (Allactoneura spp.), fruit fly (Drosophila spp.), rove beetles, noctuid moths, collembolans and mites(Tyrophagus spp.) were found infesting oyster mushroom in different months of the year. Pest incidence was found upto 100% during the rainy season (May, June, July and August). Among all, Triplax spp. and Bradysia spp. were found to be the most destructive pests of oyster mushroom; which were present throughout the year and in turn were responsible for reduction in the marketable yield. A significant positive correlation wasobserved between the population of beetle, Triplax spp. and maximum temperature (r=0.430), minimum temperature (r=0.425) and relative humidity (r=0.352). A significantpositive correlation was also found between populations of sciarid fly and maximum temperature (r=0. 541) as well as relative humidity (r=0. 371). This is a first comprehensive study of its kind, where the detailed pest complex of oyster mushroom in northeast India, their damage pattern and population dynamics throughout the year has been documented. Mushroom being a perishable edible food, this study would have immense importance for understanding the mushroom pest complex further for designing of effective management strategies against the major pests.